Acute-phase initiation of cardiac rehabilitation and clinical outcomes in hospitalized patients for acute heart failure. (1st October 2021) - Kaneko, Hidehiro; Itoh, Hidetaka; Kamiya, Kentaro; Morita, Kojiro; Sugimoto, Tadafumi; Konishi, Masaaki; Kiriyama, Hiroyuki; Kamon, Tatsuya; Fujiu, Katsuhito; Michihata, Nobuaki; Jo, Taisuke; Takeda, Norifumi; et al.
Abstract: Background: Extensive data support the clinical benefit of cardiac rehabilitation (CR) for patients with chronic heart failure (HF). However, whether CR could be beneficial for patients hospitalized for acute heart failure remains unclear. Methods: We retrospectively analyzed data from the Diagnosis Procedure Combination database, a nationwide inpatient database. We included patients hospitalized for HF, who were aged ≥20 years and with New York Heart Association class ≥II, between January 2010 and March 2018. We excluded patients with length of hospital stay ≤2 days, those undergoing major procedures under general anesthesia, those requiring advanced mechanical supports within 2 days after admission, and those with disturbance of consciousness. Propensity score matching and instrumental variable analyses were conducted to compare clinical outcomes between the patients with and without acute-phase initiation of CR defined as initiation of CR within two days after hospital admission. Results: Among 430, 216 eligible patients, 63, 470 patients (14.8%) received the acute-phase initiation of CR. Propensity score matching created 63, 470 pairs and found that the acute-phase initiation of CR was associated with lower in-hospital mortality (odds ratio [OR] 0.76, 95% confidence interval [CI] 0.73–0.80), shorter hospital stay and lower incidence of 30-day readmission due to HF. The instrumental variable analysis also showed patients with acute-phase initiation of CR was associated with lower in-hospital mortality than those without (OR, 0.73; 95% CI, 0.68–0.79). Conclusion: Our analysis suggested a potential benefit of acute-phase initiation of CR for short-term clinical outcomes in hospitalized patients with acute HF. Graphical abstract: Unlabelled Image Highlights: We studied 430, 216 acute heart failure patients using a nationwide inpatient database. PS matched analysis showed that early initiation of CR was associated with lower in-hospital mortality. Early initiation of CR was also associated with shorter hospital stay, and lower 30-day readmission due to HF. Instrumental variable analysis also showed that early initiation of CR was associated with lower in-hospital mortality.